Transvaskuläre Ablation des hepatozellulären Karzinoms: ist Chemotherapie alles? - Radeleff, Boris; Stampfl, Ulrike; Sommer, Christof-Matthias; Bellemann, Nadine; Hoffmann, Katrin; Ganten, Tom M.; Ehehalt, Robert; Kauczor, Hans-Ulrich (Der Radiologe, 2012)
Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide and represents the main cause of death among European patients with liver cirrhosis. Only 30-40% of patients diagnosed with HCC are candidates for curative treatment options (e.g. surgical resection, liver transplantation or ablation). The remaining majority of patients must undergo local regional and palliative therapies.Transvascular ablation of HCC takes advantage of the fact that the hypervascularized HCC receives most of its blood supply from the hepatic artery. In this context transvascular ablation describes different therapy regimens which can be assigned to four groups: cTACE (conventional transarterial chemoembolization), bland embolization (transarterial embolization TAE), DEB-TACE (TACE with drug-eluting beads, DEB) and SIRT (selective internal radiation therapy, radioembolization).Conventional TACE is the most common type of transvascular ablation and represents a combination of intra-arterial chemotherapy and embolization with occlusion of the arterial blood supply. However, there is no standardized regimen with respect to the chemotherapeutic drug, the embolic agent, the usage of lipiodol and the interval between the TACE procedures. Even the exact course of a cTACE procedure (order of chemotherapy or embolization) is not standardized. It remains unclear whether or not intra-arterial chemotherapy is definitely required as bland embolization using very small, tightly calibrated spherical particles (without intra-arterial administration of a chemotherapeutic drug) shows tumor necrosis comparable to cTACE.For DEB-TACE microparticles loaded with a chemotherapeutic drug combine the advantages of cTACE and bland embolization. Thereby, a continuing chemotherapeutic effect within the tumor might cause a further increase in intratumoral cytotoxicity and at the same time a decrease in systemic toxicity.
Gesehen am 26.11.2018